2001
DOI: 10.1034/j.1600-051x.2001.028006544.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of interleukin‐1β and neutrophil elastase activity in gingival crevicular fluid during experimental gingivitis

Abstract: Overall, both IL-1beta and EA showed an increase from baseline throughout the whole study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 27 publications
10
53
1
3
Order By: Relevance
“…In this process, the same cell must respond multiple times to the occupancy of its chemoattractant receptors by increasing concentrations of the attractant until the origin of that attractant is reached. Results reported previously (16,22) and shown here by our techniques, as well as binding and oxidative burst elicitation studies reported previously by others (25,49), have shown that the high-affinity fMLP receptor fPR1 of naïve, unprimed PMN is saturated and elicits maximal cytoplasmic signals at 10 Ϫ7 M fMLP and that higher concentrations bind to the low-affinity fPR2 (7,25,49) and initiate the oxidative burst and elastase release.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this process, the same cell must respond multiple times to the occupancy of its chemoattractant receptors by increasing concentrations of the attractant until the origin of that attractant is reached. Results reported previously (16,22) and shown here by our techniques, as well as binding and oxidative burst elicitation studies reported previously by others (25,49), have shown that the high-affinity fMLP receptor fPR1 of naïve, unprimed PMN is saturated and elicits maximal cytoplasmic signals at 10 Ϫ7 M fMLP and that higher concentrations bind to the low-affinity fPR2 (7,25,49) and initiate the oxidative burst and elastase release.…”
Section: Discussionsupporting
confidence: 56%
“…A 5 mM solution of elastase substrate V was prepared in distilled H 2 O and aliquoted for storage at Ϫ20°C until use. Ten microliters of this 5 mM solution of MeO-Succ-Ala-Ala-Pro-Val-AMC was added to a cuvette containing KRP (pH 7.4) at 37°C, followed by 2 ϫ 10 6 PMN (final volume, 1 ml), with stirring for 2 min (16,22,28,43). After this equilibration phase, the desired volume of fMLP or IC was injected.…”
Section: Methodsmentioning
confidence: 99%
“…dental tedavilerin etkileri ele alınmayacaksa) çalışma-lara dahil edildiği görülmektedir. 4,15,102 Bunun nedeni bu tarz etkenlerin DOS karakteristiğini etkileyebilme potansiyelidir. Örneğin bir araş-tırmada porselen laminate veneer kronların DOS miktarını artırabileceği gösterilmiştir.…”
Section: Dental Tedavilerunclassified
“…IL-1b is important in periodontal tissue destruction and its level is indicative of the activeness of disease. 18,19 A site specific increase in IL-1b has been observed in an experimental gingivitis model. 20 The chemokine (C-C motif) ligand 28 (CCL28) is a novel marker for the diagnosis of gingivitis and periodontitis.…”
Section: Introductionmentioning
confidence: 99%